PENERAPAN MODEL DISCOVERY LEARNING TIPE SHARED DAN WEBBED UNTUK MENINGKATKAN PENGUASAAN KONSEP DAN KPS SISWA - Muhammad Yusuf; Ana Ratna Wulan (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2016)
Abstract The research aimed to analyze the improvement of students’ concept mastery and science process skills through the implementation of discovery learning using integrated instruction of shared and webbed types on the topic of Global Warming. The method adopted was quasi experiment with the matching-only pretest-posttest control group design. The research instruments used were a test consisted of multiple choice questions on concept mastery and science process skills, an observation form of the implementation of instruction for teachers and students, an observation form for the implementation of science process skills for students, and a questionnaire on teachers and students’ response on the overall teaching and learning process. Research results showed that there was a significant difference between the use of integrated learning model of shared and webbed types in improving students’ concept mastery. Further results demonstrated that there was no significant difference in the use of integrated learning of shared-integrated and webbed-integrated types in improving students’ science process skills. In addition, results of teachers’ and students’ response questionnaires reveal good responses to the learning model. Abstrak Penelitian ini bertujuan untuk menganalisis peningkatan penguasaan konsep dan keterampilan proses sains (KPS) peserta didik melalui penerapan model pembelajaran discovery learning menggunakan pembelajaran keterpaduan tipe shared dan webbed pada materi Pemanasan Global. Metode penelitian yang digunakan adalah Quasi Experiment dengan The Matching-Only Pretest-Posttest Control Group Design. Instrumen penelitian yang digunakan adalah tes penguasaan konsep dan tes KPS berbentuk tes tertulis jenis pilihan ganda, lembar observasi keterlaksanaan pembelajaran bagi guru dan peserta didik, lembar keterlaksanaan KPS bagi peserta didik, serta angket tanggapan guru dan peserta didik. Hasil penelitian menunjukkan terdapat perbedaan yang signifikan antara penggunaan model pembelajaran discovery learning tipe keterpaduan shared dengan tipe keterpaduan webbed untuk meningkatkan penguasaan konsep peserta didik. Hasil lainnya menunjukkan tidak terdapat perbedaan yang signifikan antara penggunaan model pembelajaran discovery learning tipe keterpaduan shared dengan tipe keterpaduan webbed untuk meningkatkan keterampilan proses sains peserta didik. Hasil angket tanggapan guru dan peserta didik memberikan tanggapan baik terhadap model pembelajaran. Permalink/DOI: http://dx.doi.org/10.15408/es.v8i1.1730